PW 2266 Road traffic injuries in nepal: a study of causes, patterns and control measures. (November 2018) - Katuwal, Khadga; Simkhada, Padam; Gee, Ivan; Pant, Puspa
Abstract : Background: According to the World Health Organisation (WHO) road traffic injuries (RTIs) are significant burden in public health which adds 1.3 million deaths each year worldwide. It is predicted that it will become fifth leading cause of death by 2030. RTIs have become a silent 'epidemic' in Nepal with highest fatality rate in Southeast Asia Region revealed as 9th major cause of death. It is expected to rise as a combined result of increasing motorisation and rapid urbanisation in parallel. Objectives: To quantify, characterise and interpret trends in road crashes and RTIs in Nepal in the past five fiscal years (2012/13–2016/17). Methods: Mixed-method approach. Descriptive analysis of police records of road crashes was performed. In-depth interviews were conducted with 25 key stakeholders using semi-structure checklist to collect qualitative information and analysed using thematic approach. The result from both studies were utilised to triangulate both primary and secondary data. Results: Police record shows that a total of 73 540 crashes occurred throughout the country in five fiscal years resulting 9808 deaths and 59 501 injuries. On average 5 road users killed each day, male to female fatalities ratio is found 3.3:1 and involved economically active population aged 15–49 years. Almost 71.89% of crashes occur during daytime, involved two-wheeled vehicles (38%) in the country. 89% of the crashes occurred with the driver's carelessness; 3.50% drunk driving; involved young drivers (21–40 years) in the countrywide road. The common view of the stakeholders on the causes of RTIs was violation of traffic rules from both drivers and other road users. Majority of the stakeholders suggested that RTIs would decrease significantly if enforced heavier fine system against traffic rule violations and conduct traffic awareness programmes. Conclusion: Factors resulting to RTIs can be prevented by improving in road facilities and law-enforcement against violation of traffic rules.